Perspectives of nurse graduates, hospital managers and mentors regarding transition support needs during compulsory community service in South Africa - Nicholin Scheepers; Siedine K. Coetzee; Hester C. Klopper (Elsevier, 2022)
Aim: The study addresses transition support needs of nurse graduates during their compulsory community service, giving the perspectives of nurse graduates, hospital managers, and mentors. Method: A qualitative descriptive design was applied, with participants from three hospitals in South Africa. Nineteen nurse graduates participated in three focus groups, and three nurse managers, five unit managers and twelve mentors participated in individual interviews. Data were analysed through open coding using thematic analysis. Results: Four themes emerged: Structured compulsory community service programme for nurse graduates; nursing staff support during compulsory community service; learning opportunities during compulsory community service; and theory-practice gap in nursing education. Conclusion: A structured compulsory community service for nurses can improve transition for nurse graduates in South Africa. The South African Nursing Council should develop guidelines on implementation of community service, while collaboration between nursing education institutions and hospitals can close the theory-practice gap.